Circadian Rhythm and ST-Segment Elevation Myocardial Infarction: Insights From the Third Gulf Registry of Acute Coronary Events (Gulf RACE-3Ps). (April 2019) - Albackr, Hanan B.; AlHabib, Khalid F.; AlShamiri, Mostafa Q.; Ullah, Anhar; Al Subaie, Fahad A.; Alghamdi, Abduljabar G.; Alfaleh, Hussam; Kashour, Tarek; Al Suwaidi, Jassim; Alsheikh-Ali, Alawi A.; Almahmeed, Wael; Salam, Amar M.
Circadian rhythms have been identified in multiple physiological processes that may affect cardiovascular diseases, yet little is known about the impact of circadian rhythm on acute ST-segment elevation myocardial infarction (STEMI) onset and outcomes in the Middle East. The relationship between time of symptom onset during the 24-hour circadian cycle and prehospital delays and in-hospital death was assessed in 2909 patients with STEMI presenting in 6 Arabian Gulf countries. A sinusoidal smoothing function was used to show the average circadian trends. There was a significant association between time of symptom onset and the circadian cycle. The STEMIs were more frequent during the late morning and early afternoon hours ( P < .001). Patients with pain onset from 0.00 to 5:59 had median prehospital delays of 150 minutes versus 90 minutes from 6:00 to 11:59 and 12:00 to 17:59, respectively ( P < .001). Although there was no significant difference in mortality between the 4 groups ( P = .230), there was a significant association between time of symptom onset as sinusoidal function and in-hospital mortality ( P = .032). Patients with STEMI in the Middle East have significant circadian patterns in symptoms onset, prehospital delay, and timeliness of reperfusion. A circadian rhythm of in-hospital mortality was found over the 24-hour clock of symptom onset time.